Socio-economic and Environmental Sustainability of Ecotourism Implementation: A Study in Ubud Monkey Forest-Bali, Indonesia - Omar Sambou; Harsuko Riniwati; Zaenal Fanani (Program Pascasarjana, 2019)
Ecotourism is the fastest growing sector in the global tourism industry and provides for environmental conservation, socio-economic development, cultural preservation, employment and empowerment of indigenous people of ecotourism destinations. This study seeks to find the socio-economic and environmental sustainability of ecotourism practices in Ubud Monkey Forest-Bali under the three dimensions of sustainable development; economic progress, environmental protection and conservation, and socio-cultural preservation. Both quantitative and qualitative research methodologies used with the following conduct: (1) Questionnaire administration, (2) Interviews, and (3) Observations. Data was analized using Content Analysis and Multidimensional scaling (MDS) techniques to describe: (1) Â the susainabiliti of ecotourism in Is ecotourism in Ubud Monkey Forest (2) sustainability index of each of the dimensions under study in Ubud Monkey Forest, and (3) describes the level of sensitivity of sustainability of each dimension in Ubud Monkey Forest. The Kite Diagram of Sustainability Analysis presents that the sustainability status of all the used dimension which classified as sustain. The overall sustainability status of ecotourism is sustainable with an index of 76.49. The most sustainable dimension is education and recreation, while the least is the participation dimension. It shows that the dimensions under study support sustainability in ecotourism. The results of this study confirmed that within the parameters of the study, the forest maintained an ecological balance, socio-economic advancement, and cultural preservation. Ecotourism has high attraction potentials for both tourist and local businesses while impacting less on the culture, environment and the traditional practices of the Balinese people. Notwithstanding, there is a general problem of land-use change and waste management in Bali.Keywords: Ecotourism, Environment, Monkey Forest, Socio-economic, Sustainability.